1995
DOI: 10.1007/bf00293633
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cold shock proteins in Bacillus subtilis

Abstract: The cold shock response in the Gram-positive soil bacterium Bacillus subtilis is described. Cells were exposed to sudden decreases in temperature from their optimal growth temperature of 37 degrees C. The B. subtilis cells were cold shocked at 25 degrees C, 20 degrees C, 15 degrees C, and 10 degrees C. A total of 53 polypeptides were induced at the various cold shock temperatures and were revealed by two-dimensional gel electrophoresis. General stress proteins were identified by a comparative analysis with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
1

Year Published

1997
1997
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 25 publications
2
39
1
Order By: Relevance
“…(1) and the mesophile Lactococcus lactis subsp. lactis (37) or B. subtilis (29) had no lag phase consequent to a cold treatment. Their growth continued at an intermediate rate followed by a growth rate characteristic of final low temperature.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…(1) and the mesophile Lactococcus lactis subsp. lactis (37) or B. subtilis (29) had no lag phase consequent to a cold treatment. Their growth continued at an intermediate rate followed by a growth rate characteristic of final low temperature.…”
Section: Discussionmentioning
confidence: 95%
“…In the same way, this criterion of classification according to temperature range of growth fails to predict the consequences of cold shocks on protein synthesis. Indeed, after cold shock treatments, the relative rate of synthesis of most cellular proteins was maintained in P. fragi, as for other psychrotrophs such as B. psychrophilus (49) or A. globiformis (3), but also for mesophiles such as B. subtilis (29). On the contrary, the mesophile E. coli (18), but also the psychrotrophs L. monocytogenes and L. innocua (38), have a dramatic decrease in protein synthesis immediately after a downshift in temperature.…”
Section: Discussionmentioning
confidence: 99%
“…About 60 proteins of B. subtilis have been identified on 2-D polyacrylamide gels so far (see also Graumann et al, 1996;Lottering & Streips, 1995 ;Miller et al, 1991 ;Schmid et al, 1997;H. Antelmann and others, unpublished).…”
Section: Discussionmentioning
confidence: 99%
“…Although synthesis of the majority of proteins decreases after a temperature downshift, the level of a specific group of proteins increases under these conditions in B. subtilis (Lottering & Streips, 1995 ;Graumann et al, 1996). Using two-dimensional (2D) protein gel electrophoresis, it has been demonstrated that the synthesis of at least 37 proteins of B. subtilis increases after a temperature shift from 37 to 15 mC (Graumann et al, 1996).…”
Section: Introductionmentioning
confidence: 99%